Pengembangan Kurikulum Pendidikan Agama Islam dalam Perspektif Pendidikan Dasar dan Madrasah Ibtidaiyah dalam Mengembangkan Karakter Siswa - Monica Mulyani Batubara; Ahmad Yain; Elisah Pahutar; Partahian Partahian; Ahmad Muda Harahap (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
This study aims to analyze the development of the Islamic Religious Education (PAI) curriculum from the perspective of elementary and Madrasah Ibtidaiyah education in developing student character. The study uses a qualitative approach with a literature study type (library research) that examines various scientific sources in the form of books, journal articles, and documents related to the curriculum and character education. Data collection techniques are carried out through searching, selecting, and classifying relevant literature, while data analysis uses content analysis and descriptive-critical methods to produce a comprehensive conceptual synthesis. The results of the study indicate that the development of a character-based PAI curriculum must be carried out integratively by combining cognitive, affective, and psychomotor aspects in all learning components. Character values such as honesty, responsibility, discipline, and social concern need to be internalized through open materials, learning strategies, and school culture. In addition, the role of teachers as role models and learning facilitators is a key factor in the success of the curriculum implementation. This study emphasizes the importance of synergy between the curriculum, the learning process, and the educational environment in shaping student character. Thus, this study provides a theoretical contribution in the development of a character-based PAI curriculum and applies it practically to improve the quality of education in Madrasah Ibtidaiyah.